The cardiac rate and the intensity of the physical activity of the assistant referee during a soccer match - Alberto Inácio da Silva; Ciro Romelho Rodriguez-Añez (Journal of Physical Education (Maringá), 2008)
The exercise intensity is one of the most important training control variables, as the performance of exercises with an intensity lower than that of the competition does not promote the desirable adaptations to the organism. This study aimed at analyzing the physical activity intensity of the soccer assistant referee during a match, by measuring his cardiac rate. A sample of ten 30±5 year-old-soccer referees, with an average weight of 77±3 kg, and acting as assistant referees in the city of Curitiba was observed. Their cardiac rate was measured during official games with a Vantage XL POLAR cardiac rate monitor model. The data analyzed indicated a 65 to 150 bpm cardiac rate variation, a 102 bpm mean cardiac rate, a maximal cardiac rate of 193 ±11 bpm, and an anaerobic threshold cardiac rate of 176 ±14 bpm during the match. The differences between the first and the second time of the match were not statistically significant (p > 0.05). Therefore, it could be verified that the assistant referee’s physical activity is aerobic, since his mean cardiac rate during the match was 58% lower than the anaerobic threshold cardiac rate. Another result that reinforces this observation is the fact that the mean cardiac rate is only 52% lower than the maximal one. This intensity characterizes a moderate physical activity.